Exploring the dimensions of service quality in higher education research - Ramaiyah, A.; Md. Zain, A.N.; Ahmad, Halim (2007)
The dimension of service quality is still debated among the academic researchers. The purpose of this study is to examine the different dimensions used and applied in the process of evaluating the service quality under in the higher education sector. Eight different dimensions of service quality were examined to identify the similarities and the differences. The outcome of the findings indicates that each set of dimensions developed are relevant according to different expectations of customers. This study is expected to pave way for researchers who are interested to conduct further studies on the implications of service quality in Malaysian higher education environment.